The Fate of Deep-Sea Coral Reefs on Seamounts in a Fishery-Seascape: What Are the Impacts, What Remains, and What Is Protected? - Williams, Alan; Althaus, Franziska; Maguire, Kylie; Green, Mark; Untiedt, Candice; Alderslade, Phil; Clark, Malcolm R.; Bax, Nicholas; Schlacher, Thomas A. (Frontiers in Marine Science, 2020)
Environmental harm to deep-water coral reefs on seamounts is widely attributed to bottom trawl fishing. Yet, accurate diagnoses of impacts truly caused by trawling are surprisingly rare. Similarly, comprehensive regional assessments of fishing damage rarely exist, impeding evaluations of, and improvements to, conservation measures. Here we report on trawling impacts to stony coral reefs in a regional (10s to 100s of kms) fishery seascape off Tasmania (Australia). Our study was based on 148 km of towed camera transects (95 transects on 51 different seamounts with 284,660 separate video annotations and 4,674 ‘on-seamount’ images analysed), and commercial logbook data indexing fishing effort on and around seamounts. We detect trawling damage on 88% (45 of 51) of seamounts. Conversely, intact coral reefs persist in refuge areas on about 39% (20 of 51) of the seamounts, and where reefs extend onto a rocky seabed adjacent to seamounts. Depth significantly shapes the severity of trawl damage. The most profound impacts are evident on shallow seamounts (those peaking in < 950 m depths) where recent and repeated trawling reduced coral reefs of shallow stony coral species to rubble, forming extensive accumulations around seamount peaks and flanks. At intermediate depths (~950-1,500 m), trawling damage is highly variable on individual seamounts, ranging from substantial impacts to no detection of coral loss. Deep seamounts (summit depth > 1,500 m) are beyond the typical operating depth of the trawl fishery and exceed the depth range of reef-forming corals in the region. Accurately diagnosing the nature and extent of direct trawling impacts on seamount stony coral reefs must use stringent criteria to guard against false positive identifications of trawl impact stemming from either (1) misidentifying areas that naturally lacked coral reef as areas where coral had been removed, or (2) attributing trawling as the cause of natural processes of reef degradation. The existence of sizeable reef refuges in a complex mosaic of spatially variable fishing effort suggests that more nuanced approaches to conservation may be warranted than simply protecting unfished areas.